Atezolizumab Plus Bevacizumab in Patients with Unresectable Hepatocellular Carcinoma: Real-World Experience From a US Community Oncology Network - Cosgrove,David; Tan,Ruoding; Osterland,Andrew; Hernandez,Sairy; Ogale,Sarika; Mahrus,Sami; Murphy,John; Wilson,Thomas; Patton,Gregory; Loaiza-Bonilla,Arturo; Singal,Amit (Journal of Hepatocellular Carcinoma, 2025)
David Cosgrove,1 Ruoding Tan,2 Andrew J Osterland,3 Sairy Hernandez,2 Sarika Ogale,2 Sami Mahrus,2 John Murphy,3 Thomas Wilson,3 Gregory Patton,3 Arturo Loaiza-Bonilla,4 Amit G Singal5 1Medical Oncology, Compass Oncology/The US Oncology Network, Vancouver, WA, USA; 2Genentech, South San Francisco, CA, USA; 3Real-World Research, Ontada, Boston, MA, USA; 4Medical Oncology, Capital Health Cancer Center, Pennington, NJ, USA; 5Department of Internal Medicine, University of Texas Southwestern Medical Center, Dallas, TX, USACorrespondence: David Cosgrove, Compass Oncology, 210 SE 136th Ave, Vancouver, WA, 98684, USA, Email David.Cosgrove@compassoncology.comPurpose: Atezolizumab plus bevacizumab (atezo-bev) is a preferred first-line (1L) systemic therapy option for unresectable hepatocellular carcinoma (uHCC). However, evidence of its effectiveness in real-world clinical practice, including in patients with impaired liver function, remains limited.Patients and Methods: This retrospective observational study included adult patients who initiated 1L atezo-bev for uHCC within The US Oncology Network between 1/1/2019 and 8/31/2022 using structured and unstructured electronic health records data. Overall survival (OS) and real-world progression-free survival (rwPFS) were assessed using Kaplan-Meier methods for the overall cohort and in a subgroup of â€œtrial-likeâ€ patients with characteristics that were consistent with those of the IMbrave150 Trial (ECOG performance status 0â€“ 1, Child-Pugh class A, albumin-bilirubin grade 1â€“ 2).Results: Overall, 374 patients met eligibility criteria (mean age 68.8 years, 78.9% male, 31% Child-Pugh class B-C among reported, 18% ECOG performance status â‰¥ 2 among reported), of whom 132 patients comprised the trial-like subgroup. At a median follow-up of 5.6 months, median (95% CI) OS was 13.2 (9.5, 15.9) months and rwPFS was 6.4 (5.1, 7.7) months. In the trial-like subgroup, median (95% CI) OS was 16.5 (13.2, NR) months and rwPFS was 9.4 (5.7, 12.5) months.Conclusion: Atezo-bev was used ...